Effect of photoactive carbon nitride and titanium dioxide features on HKUST-1 depositions and catalytic consequences during CO2 conversion in water - P.R. Nimax; S. Vaquero-Vílchez; C. Múgica; H. Gomez; I. Agirrezabal-Telleria (Journal of CO2 Utilization)
“CO2 storage is one of the biggest challenges in controlling climate change. It can either be stored permanently or recycled into chemicals for which photoreduction of CO2 is a promising method by providing a way to enable conversion into high value chemicals with sunlight. Photoactive supports, such as carbon nitride or titanium dioxide catalyze this conversion and mesoporous materials can enhance substrate uptake by increasing surface area and adsorption. Metal-organic frameworks (MOF) deposition on such materials enables to increase substrate specificity and direct conversion into desired products. Since MOFs are affected by environmental factors, such as pH, temperature or co-ligands during their formation and interaction, structural differences in photoactive support will impact behavior and affect productivity of acetaldehyde and ethanol from CO2 and water within HKUST-1@support heterojunctions. This investigation compares morphological and photocatalytic effects of growing HKUST-1 on graphitic carbon nitride, mesoporous carbon nitride and TiO2. By adding MOF layers in a stepwise process, we investigate surface binding and interaction on each support in photoreduction of CO2 in a closed batch system under room temperature. Such methods allow us to study the effect of support-interactions on MOF growth and cross-reference to the observed photocatalytic activity. This leads to a shift towards ethanol productivity with selectivity of up to 63 % compared to acetaldehyde in the support itself, directing production towards specific products by adding MOF on photoactive support.”